Comparison of anatomical information of lumbar T2 TSE MRI images with nex variation between use and without sense - Safitri, Ara Novita; Susanto, Fani; Rahardian, Arga Pratama; Oviyanti, Pradana Nur; Samudra, Alan (Science Midwifery, 2025)
Due to the long scan time, patients often report pain and discomfort during lumbar MRI examination. NEX and SENSE are two parallel imaging parameters that affect scan time. However, the resulting image information is also affected by NEX and SENSE. Therefore, this study examines the information between NEX variations with and without SENSE on anatomical images and their relationship with scan time on lumbar T2 TSE MRI examinations. This study is quantitative and uses an experimental method. The sample in this study was 10 volunteers who would be given 6 treatments, namely NEX 1 variation without SENSE, NEX 1 with SENSE, NEX 2 without SENSE, NEX 2 with SENSE, NEX 3 without SENSE, and NEX 3 with SENSE on Lumbar T2 TSE MRI examinations in January 2025. Using the Visual Grading Analysis (VGA) method, two radiology specialist observers analyzed the image results. Then the Cohen's Kappa consistency test was carried out and the Friedman test was used to verify the questionnaire results statistically. This study shows that there is a significant difference in the value of image information between NEX 1 variations of vertebral body anatomy with and without SENSE. While in the anatomy of the Intervertebral Disc, Ligament, Spinal Cord, and Spinal Stenosis did not show a significant difference in each variation of NEX with and without SENSE. For scan time, with NEX variations using SENSE requires a shorter scan time compared to without the use of SENSE.